Sex‐related differences in cognitive trajectories in older individuals with type 2 diabetes and overweight or obesity and the role of APOE4: Findings from the Look AHEAD and Look AHEAD‐MIND studies: Epidemiology / Risk and protective factors in MCI and dementia. (7th December 2020) - Espeland, Mark A; Bennett, Wendy; Carmichael, Owen T; Chao, Ariana; Dutton, Gareth; Hayden, Kathleen M; Hugenschmidt, Christina E; Kahn, Steven; Luchsinger, Jose; Neiberg, Rebecca H; Roman‐Ashby, Glorian; Olson, Kayloni; et al.
Abstract: Background: Women's cognitive performance, particularly in the domains of verbal learning and memory, generally exceeds that of men. Among older individuals with diabetes and overweight/obesity, two conditions known to accelerate cognitive aging, it is unknown how these sex‐related differences in cognitive functioning unfold over time, i.e. whether any advantages seen in women result from less steep trajectories of cognitive decline than men, and whether any differences in rates of decline are moderated by the APOE4 genotype. Method: A standardized battery of cognitive function tests was administered 2 to 4 times over the course of up to 10 years (mean 5.3 years) among 2583 adults (62% women) who averaged 68 years of age at their first assessment. Mixed effects models were used to compare cognitive function scores (verbal learning, executive function, and processing speed) at the first assessment and rates of cognitive decline over time between women and men, with covariate adjustment for potentially confounding risk factors for cognitive decline. Result: At their first assessment, women significantly outperformed men on tasks of verbal memory and processing speed (both p<0.001), but not executive function (p=0.38). These differences were evident for those both with and without the APOE4 genotype. Over follow‐up, women and men had similar rates of cognitive decline in these domains, overall and among those without the APOE4 genotype (all p>0.05). However, the APOE4 genotype was associated with significantly greater rates of decline among women than men for verbal learning (37% vs 8% increase, p=0.04) and processing speed (28% increase vs 5% decrease, p=0.004), but similar increased rates of decline in executive function (p=0.67). Conclusion: Female sex is associated with better cognitive functioning than male sex in key domains among older individuals with diabetes and overweight/obesity. Overall, this relative advantage is maintained over time among women without the APOE4 genotype. However, among those with the APOE4 genotype, rates of decline in verbal learning and processing speed are greater among women compared with men.